The Quality of Services of Iran University Hospitals Based on SERVQUAL's Evaluation Model: A Systematic Review and Meta-Analysis - Gilavand, Abdolreza; Torabipour, Amin (Frontiers in Public Health, 2022)
Introduction: Systematic evaluation of the quality of services provided in hospitals and healthcare centers is the first step towards standardization and improving their quality. Methods: In this systematic review (meta-analysis) study, the information was collected by searching for the articles published in well-known Iranian and international and through searching for the keywords of SERVQUAL, services quality, gap, hospital, patients, Iran, and without language and time restrictions. Results: A total of 18 articles were reviewed and opinions of 4,714 people who referred to hospitals and healthcare centers affiliated to Iran University of Medical Sciences during the past 10 years from 2010 to 2019 were examined in this study. The results showed that there was a quality gap in all 5 dimensions between the current status and desirable status of patients and based on a maximum score of 5, responsiveness (1.04), and assurance (0.99), empathy (0.95), reliability (0.91) and physical or tangible factors (0.86) were ranked first to fifth, respectively. According to the random effect model, the mean score of patients' perceptions and expectations and the gap between them was 3.59 (CI 95%: 3.73, 3.46), 4.66 (CI 95%: 4.33 AND 4.66), and 0.86 (CI 95%: 1.00, 0.72), respectively. Conclusion: The patients' expectations in university hospitals were higher than their perceptions. Therefore, it is recommended for Ministry of Health and Medical Education of Iran to monitor periodically the quality of hospitals while focusing on students’ and patients’ satisfaction and pay attention to dimensions that have the highest quality gap.